THE EFFECTIVENESS OF USING DIRECT METHOD COMPARED WITH TOTAL PHYSICAL RESPONSE IN TEACHING VOCABULARY ON HOBBIES AND DAILY ACTIVITIES TO SIXTH GRADERS STUDENTS - Ratno, Ratno (PAWIYATAN, 2013)
This study is an experimental research. In this study, the writer limits the discussion by stating the following problems:Ã¢â¬Â How well do Elementary students produce their vocabulary after being taught using Total Physical Response?Ã¢â¬Â, Ã¢â¬ÅHow well do Elementary students produce their vocabulary after being taught using Direct Method?Ã¢â¬Â, Ã¢â¬ÅIs there any difference result of teaching vocabulary to Elementary students, using Direct Method and Total Physical Response?Ã¢â¬Â. The aim of this experimental research is first; to analysis how well the Direct Method influences the students in learning vocabulary. Second, how well the Total Physical Response influences the students in learning vocabulary. So, we can determine whether there is significance difference in the achievement between students who were taught using Direct Method and taught by using Total Physical Response. There were three steps in conducting this experimental research; choosing the sixth graders of MI Al Iman Gunung Pati as the population, taking two groups of the students as samples; one as an experimental group and the other as a control group that consist of 16 students each group and after that conducting the real experiment. To obtain the data, the writer used post-test only in implement the step. The result of this research showed that the experimental group got better achievement than the control group. Dealing with this experimental research, the writer suggests that Direct Method can be used as a method in teaching vocabulary to sixth graders of elementary school. The purpose is to create a new situation that makes students interested in learning English.ÃÂ Keywords: Teaching, Elementary School, Vocabulary, Direct Method, and Total Physical Response